Hydroxychloroquine Blood Levels Predict Hydroxychloroquine Retinopathy. Issue 3 (7th January 2020) - Petri, Michelle; Elkhalifa, Marwa; Li, Jessica; Magder, Laurence S.; Goldman, Daniel W.
Abstract : Objective: In 2016, the American Academy of Ophthalmology (AAO) changed the recommended daily dose of hydroxychloroquine (HCQ) from 6.5 mg/kg to <5 mg/kg. However, it is not clear that the lower prescribed dose of HCQ will have the same efficacy for systemic lupus erythematosus (SLE) activity or the same role in protecting against cardiovascular risk factors and thrombosis. This study was undertaken to address the frequency of HCQ retinopathy and the role of HCQ blood levels in identifying those individuals who are at a greater future risk of retinopathy. Methods: HCQ blood levels in 537 patients with SLE from a large clinical cohort were repeatedly measured, and patients were tested for HCQ retinopathy. We assessed the risk of retinopathy according to clinical characteristics and blood levels of HCQ. Results: The overall frequency of retinopathy was 4.3% (23 of 537 patients). There was a 1% risk of retinopathy in the first 5 years of HCQ treatment, 1.8% from 6 to 10 years, 3.3% from 11 to 15 years, 11.5% from 16 to 20 years, and 8.0% after 21 years of use. We found that older age ( P < 0.0001), higher body mass index ( P for trend = 0.0160), and longer duration of HCQ intake ( P = 0.0024 and P for trend = 0.0006) were associated with a higher risk of HCQ toxicity. Higher blood levels of HCQ predicted later HCQ retinopathy ( P = 0.0124 and P = 0.0340 for mean and maximum HCQ blood levels, respectively). Conclusion: Our data prove the utility of assessing blood levels of HCQ in the prediction of retinopathy. This would allow clinicians to either decrease the dose or increase monitoring in those patients with high HCQ blood levels.